Hamka, Zhenghe, and Indonesian Islam - Al Akbar, Nuruddin (Journal of Integrative International Relations, 2019)
This study seeks to trace the centrality of the use of Zhenghe's notes and other Chinese documents in Hamka's work which discusses the development of Islam in the Indonesian archipelago (mainly in the book titled Sejarah Umat Islam). The study will focus on two things: first, discussing the central position of Zhenghe's notes for the development of historiography of Indonesian Islam in Hamka's work. Second, this study discusses the important role of Hamka in elevating the value of Chinese documents as an important historical source. Keep in mind that in the Hamka era, historical writing was still dominated by Eurocentric logic which tended to prioritise Western records compared to non- Western sources. In other words, there is a unique interaction between Hamka and Chinese records where on the one hand Chinese records can help Muslims in Indonesia reconstruct their history, but on the other hand, Indonesian Muslims elevate the value of Chinese documents in the academic world.